Pengaruh Model Pembelajaran Talking Stick terhadap Kemampuan Berpikir Kritis Peserta Didik Mata Pelajaran IPAS Kelas IV Sekolah Dasar - Rahmadhani, Fitrya Dwi; Supriyadi, Supriyadi; Rohman, Fatkhur; Rapani, Rapani (Lentera: Jurnal Ilmiah Kependidikan, 2024)
The problem in this study is the lack of critical thinking ability of the 4th IPAS class SDN 1 Jatimulyo's student. It is caused by learning is still centered on educators and the model of learning used is less varied. This study aims to identify the impact and difference in using a talking stick learning model on the IPAS student's critical ability. The method used in this study is an experiment with the design of the non- invasive design group. The population in this study is 76 students students with 49 samples. Sample retrieval techniques used is a nonsampling sampling techniques, a purposive sampling technique. Data retrieval techniques are through tests, observation, and documentation. The data was analyzed using simple regression tests and T test. The results of the study suggest that a talking stick learning model has an impact on critical thinking ability and that there is a critical thinking ability difference between experimental classes and control classes. The experimental class that uses talking stick learning models has higher critical thinking ability than the control class, so the talking stick learning model can be used as an alternate learning model to improve the critical thinking ability of students